Dynamic Modeling and Experimental Study of Involute Spline Pairs with Clearance - Wang Xiaorui; Li Bing; Miao Huihui (Jixie chuandong)
Involute splines are widely used in the transmission system of special vehicles. At present, the spline pair is regarded as rigid connection, and the interface contact state of spline pairs directly affects the characteristics of the transmission system in the environment where the dynamic characteristics of the transmission system are highly required. Considering the fit clearance of spline pairs, the engagement stiffness of spline single teeth is calculated using the cantilever beam model, and the bending-torsional coupling model of involute spline pairs is established. The Runge-Kuta method is used to solve the model, the dynamics test platform is built to verify the correctness of the analytical model, and the acceleration spectrum characteristics are analysed. The research results show that the theoretical and experimental results are consistent under different rotational frequencies, which proves the validity of the model. With the increase of the clearance, the force of each spline pair tooth decreases, and the force of each tooth is not uniform under the same clearance amount. The proposed dynamic model analysis method can provide a basis for the study of interface contact characteristics of involute splines in clearance fit.